CERTAIN ISSUES RELATED TO THE NOTION OF “OFFICIAL” - Ter-Torosyan, Nelly (State and Law, 2023)
The notion of “official” was analyzed in the scientific article. The peculiarities of the content of this concept in different legal acts were referred to. The analysis of the content of the concept of "official" is based on the study of both theoretical literature and case law.